Three cases of congenital dysfibrinogenemia in unrelated Chinese families: heterozygous missense mutation in fibrinogen alpha chain Argl6His. Issue 39 (September 2016) - Luo, Meiling; Deng, Donghong; Xiang, Liqun; Cheng, Peng; Liao, Lin; Deng, Xuelian; Yan, Jie; Lin, Faquan
Abstract : Abstract: Congenital dysfibrinogenemia (CD) is a qualitative fibrinogen disorder caused by an abnormal fibrinogen molecule structure, leading to dysfunctional blood coagulation. This study describes 3 cases of dysfibrinogenemia identified in the unrelated Chinese pedigrees. Routine coagulation screening tests were performed on the probands and their families. The antigens and functionality of fibrinogen was measured using an immunoturbidimetry assay and the Clauss method, respectively. To identify the genetic mutation responsible for these dysfibrinogens, genomic DNA extracted from the blood was analyzed using PCR amplification and direct sequencing. The presence of the mutant chains was determined using matrix-assisted laser desorption/ionization time of flight (MALDI-TOF) mass spectroscopy. Purified plasma fibrinogen of 3 probands was analyzed using SDS–PAGE, fibrinogen clottability, fibrin polymerization, fibrinopeptide release, and scanning electron microscopy (SEM). The 3 probands had a long thrombin time. Levels of functional fibrinogen were found to be very low, while the fibrinogen antigen was within the normal range. DNA sequencing revealed a heterozygous Arg16His substitution in the fibrinogen Aα chain (FGA). The mutant chains were found to be expressed using MALDI-TOF mass spectroscopy. SDS–PAGE did not reveal any difference in the molecular weights of 3 polypeptide chains between normal and abnormal fibrinogens. Fibrinogen clottability showed a slower fibrin clot formation than the healthy control. Fibrin polymerization, after addition of thrombin, showed a prolonged lag phase and decreased final turbidity. The kinetics of fibrinopeptides release revealed a decreased amount of the released fibrinopeptide A. SEM of the patient's fibrin clot was found to be abnormal. Results indicate that the 3 probands with dysfibrinogenemia were caused by mutations of Aα chain Arg16His. Mutation of this fibrinogen induced dysfunction of plasma fibrinogen.